ANALYSIS OF THE INFLUENCE OF IMPURITIES AND DEFECTS IN FIBER ON TECHNOLOGICAL PROCESSES OF SPINNING - Malikakhon N. Babaeva (European Science Publishing, 2024)
This study analyzes the impact of impurities and fibre defects on the tech-nological processes of spinning, with a focus on the fibre cleaning stages within spinning systems. The research evaluates how these impurities and defects affect yarn quality, specifically when using different types of spinning machines, in-cluding those from Rieter, Trutschler, and Marzoli. Key quality indicators, such as relative hardness, roughness, tensile strength, elongation, and the presence of thin and thick sections in yarn, are examined using Uster statistics from 2018. Through a comparative analysis of yarn produced on various spinning systems, the article provides insights into the role of impurities and defects in shaping yarn quality, contributing to more efficient processes and higher product stand-ards in textile manufacturing.
Keywords: card, yarn, ring spinning, quality, relative hardness, Uster sta-tistics 2018, roughness, Rieter, Trutschler, Marzoli, tensile strength, elongation, number of thin sections, number of thick sections, defects.